Romance screenplay project the first date: research on clan exogamy marriage of Minangkabau (Indonesia) / Anis Suraya Suhaimi - Suhaimi, Anis Suraya (Faculty of Film, Theatre and Animation, 2016)
The Minangkabau socio cultural in Indonesia has fascinated many researchers due to the matrilineality family structure and Islamic way of life. However, most of the research has been focused on matrilineality due on history and past theories. This research project offers different cultural studies approaches, through novel and film. This research project will explore the clan exogamy marriage and analyze two outstanding pieces, the film and novel of Tenggelamnya Kapal Van der Wijck in romance frame. It will be argued that culture (Minangkabau) can be studied from relevant masterpieces instead of history approaches. This research project implements Minangkabau clan and the issue of clan exogamy marriage in a screenplay project entitled The First Date. Such a new cultural studies approach could also be useful for the research of other societies in order to understand much simpler for cultural studies.